1996
DOI: 10.1002/ana.410400221
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral adrenoleukodystrophy (ALD) in only one of monozygotic twins with an identical ALD genotype

Abstract: We report on monozygotic twins with different clinical phenotypes of X-linked adrenoleukodystrophy. At the age of 10 years both boys were neurologically asymptomatic. The first cranial magnetic resonance examination showed normal findings in the first twin and parietooccipital demyelination in the second. The latter developed behavioral problems 9 months later, followed by visual impairment and gait ataxia. His cranial magnetic resonance image at the age of 11 years showed progressive demyelination. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 13 publications
2
60
0
Order By: Relevance
“…Others found that severity of the X-ALD phenotype is correlated with expression of an other peroxisomal transporter gene (ABCD4) and of the VLCFA synthase gene BG1 [52]. Recently, we reported that functional polymorphisms of genes and proteins involved in environmental factors may also be involved, as indicated by phenotypic variability in a set of monozygotic twins [55], and the disease may putatively also be triggered by CNS traumas [14].…”
Section: Modifying Factorsmentioning
confidence: 94%
“…Others found that severity of the X-ALD phenotype is correlated with expression of an other peroxisomal transporter gene (ABCD4) and of the VLCFA synthase gene BG1 [52]. Recently, we reported that functional polymorphisms of genes and proteins involved in environmental factors may also be involved, as indicated by phenotypic variability in a set of monozygotic twins [55], and the disease may putatively also be triggered by CNS traumas [14].…”
Section: Modifying Factorsmentioning
confidence: 94%
“…(n ¼ 18), frame-shift mutations (n ¼ 5), in-frame deletions (n ¼ 2), in-frame insertion (n ¼ 1), nonsense mutation (n ¼ 1), splice site mutation (n ¼ 1). Sixteen of these mutations have been published before (11,21); the remaining 12 mutations comprise nine missense mutations (A141T, Y281H, R389H, G512S, P543L, R554H, Y559H, R617H, R679R), two frame-shift mutations (del 740, del 2132) and one splice site mutation (ins 8 bp 2252). There was no correlation between the loci or kind of mutation and ACTH concentration (Fig.…”
Section: Genetic Examinationsmentioning
confidence: 99%
“…Both twins carried the same mutation in the X-linked adrenoleukodystrophy (ALD) gene, yet one developed blindness, balance problems, and loss of myelin in the brain, features typical of the progressive and lethal neurological disease, whereas the other remained healthy. The conclusion of the investigators reporting the unusual occurrence was "some nongenetic factors may be important for different adrenoleukodystrophy phenotypes" (Korenke et al 1996). That indeed was a valid conclusion in 1996, given the focus of medical genetics on DNA sequence.…”
Section: Introductionmentioning
confidence: 95%